Magnetically Guided Laser Surgery for the Treatment of Twin‐to‐Twin Transfusion Syndrome. (13th October 2022) - Lussi, Jonas; Gervasoni, Simone; Mattille, Michelle; Dreyfus, Roland; Boehler, Quentin; Reinehr, Michael; Ochsenbein, Nicole; Nelson, Bradley J; Moehrlen, Ueli
Abstract : Twin‐to‐twin transfusion syndrome (TTTS) is a severe disorder that often leads to the death of monochorionic twin fetuses, if left untreated. Current prenatal interventions to treat the condition involve the use of rigid fetoscopes for targeted laser coagulation of the vascular anastomoses. These tools are limited in their area of operation, making treatment challenging, especially in cases with anterior placentation. Herein, a robotic platform to perform this task using remote magnetic navigation is proposed. In contrast to rigid tools, the presented custom magnetic fetoscope is highly flexible, dexterous, and has considerable advantages, including safety and precision. A visual servoing algorithm that allows the surgeon to navigate in the uterus with submillimeter precision is introduced. The system has been validated on ex vivo human placentas in a setting that mimics the real intraoperative conditions. Abstract : Twin‐to‐twin transfusion syndrome (TTTS) is a severe disorder that often leads to the death of monochorionic twin fetuses, if left untreated. Herein, a robotic platform to perform TTTS surgery using remote magnetic navigation is presented. In contrast to rigid tools, the custom magnetic fetoscope is highly flexible, dexterous, and has considerable advantages, including safety and precision.